Photocatalytic oxidation of gas phase volatile organic compounds (VOCS) using nanostructure titanium dioxide based materials - Othman, Mohd. Yusuf; Mohd. Saiyudi, Noor Khaida Wati (Faculty of Science, 2007)
Various atomic ratios of metal doped TiO2 were prepared using Mn2+, Fe2+, Fe3+, Cu2+, Zn2+, Cu2+ co-doped with Fe3+ and Zn2+ co-doped with Fe3+. Photocatalytic degradation of CH2Cl2, CHCl3 and CCl4 using various atomic ratios of metal doped TiO2 showed the existence of optimum dopant ratio, which indicates the dependency of photoactivity of doped TiO2 on dopant concentration. Besides, dopants can affect the photoactivity of doped TiO2 by acting as hole/electron traps or as recombination centres. Using doped catalysts such as Fe2+/TiO2, Fe3+/TiO2, Cu2+/TiO2, Zn2+/TiO2, Cu2+/Fe3+/TiO2 and Zn2+/Fe3+/TiO2 gave higher degradation of VOCs than pure TiO2. However, adding of Mn2+ was detrimental to the process. The rate of degradation of the studied chlorinated hydrocarbons follows the order: CHCl3 > CH2Cl2 > CCl4. This indicates different VOCs will have different levels of degradation although same catalyst was used in the photocatalytic degradation experiment. In photocatalytic degaradation of CHCl3 and CCl4 mixtures, low concentration of CHCl3 and CCl4 mixtures shows higher degradation than CCl4. The Clâˆ™ radicals do not attack C-Cl bond s in CCl4, therefore, Clâˆ™ radicals formed during the illumination of UV lamp may contribute to the degradation of CHCl3. Consequently, more CHCl3 was degraded. Possible model for photocatalytic degradation of VOCs were proposed, utilizing data from fragments analysis using GC-MS. SEM/EDX, UV-Vis and ellipsometer were used to characterize the structural and optical properties of thin films. Addition of dopants shifted the absorption edge of TiO2 and this indicated the changes of band gap energy. The film thickness for all catalyst samples is between 227-251 nm and within the acceptable range of thin films (<1000 nm).